Synthesis and analysis of borophene through magnesium-activated boron using combined electrochemical exfoliation and sonication techniques - Arifur Rahman; Mohammad Asaduzzaman Chowdhury; Md Tawabur Rahman; Md Masud Rana; Mohammad Nazir Ahmed; Muhammad Ali Zinnah; M.M. Kamal Uddin (Next Nanotechnology)
Borophene, a two-dimensional (2D) monolayer of elemental boron, attracted considerable interest owing to its remarkable electronic, optical, chemical, mechanical, and catalytic properties. However, the complex structure and inherently low electrical conductivity of boron pose challenges to synthesizing borophene via electrochemical exfoliation. This study reports a magnesium-assisted electrochemical exfoliation of boron towards borophene. The structural, morphological, and chemical properties of borophene have been analyzed using various characterization techniques, including X-ray diffraction (XRD), Raman spectroscopy, field emission scanning electron microscopy (FESEM), Fourier-transform infrared spectroscopy (FTIR), UV-Vis spectroscopy, and X-ray photoelectron spectroscopy (XPS). For the effect of sonication after electrochemical exfoliation, the percentages of crystallinity as well as average crystallite size of borophene increased from 23.53 % to 58.52 % and 14.94 nm to 38.31 nm respectively. A flake-like nanostructure was observed in the synthesized borophene. Furthermore, the incorporation of magnesium into boron increased the bandgap from 1.30 eV to 1.53 eV, highlighting its potential for electronic device applications. This novel chemical route offers a promising approach for the large-scale, low-cost production of high-quality borophene, paving the way for the development of next-generation devices and cutting-edge applications.